2021
DOI: 10.1016/j.euf.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Clonal Dynamics Reveals that Two- and Three-dimensional Patient-derived Cell Models Capture Tumor Heterogeneity of Clear Cell Renal Cell Carcinoma

Abstract: Background: Extensive DNA sequencing has led to an unprecedented view of the diversity of individual genomes and their evolution among patients with clear cell renal cell carcinoma (ccRCC). Objective: To understand subclonal architecture and dynamics of patient-derived two-dimensional (2D) and three-dimensional (3D) ccRCC models in vitro, in order to determine whether they mirror ccRCC inter-and intratumor heterogeneity. Design, setting, and participants: We have established a comprehensive platform of living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Two other methods to culture ccRCC organoids have recently been described 56,57 . The first yielded organoids with a limited expansion capacity and a low rate of success.…”
Section: Discussionmentioning
confidence: 99%
“…Two other methods to culture ccRCC organoids have recently been described 56,57 . The first yielded organoids with a limited expansion capacity and a low rate of success.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, primary breast cancer organoids have been reported to faithfully recapitulate the corresponding parent tumors in morphology, histopathology, hormone receptor status, and mutational landscape ( 112 ). Organoids of other cancer types have also been subsequently established, including gastric ( 78 , 90 , 93 , 126 ), prostate ( 39 ), ovarian ( 69 ), brain ( 22 ), bladder ( 74 ), kidney ( 15 ), lung ( 114 ), and esophageal cancers ( 77 ).…”
Section: Organoid Applicationsmentioning
confidence: 99%
“…Large-scale genomic and functional analysis from various studies have shown that tumor-derived organoids can faithfully recapitulate the phenotypic and genomic features of the primary tumors both in vitro and in vivo after transplantation ( 14 , 39 , 73 , 112 , 150 ). Importantly, the tumor heterogeneity and clonal dynamics were preserved after serial passaging of PDOs, indicating that these “mini-tumors” are genetically stable with enormous clinical applicability ( 15 ). With increasing interest in the use of organoids for disease modeling, biobanking can soon be extended beyond cancer, such as intestinal and lung organoids for cystic fibrosis patients and liver organoids for patients with various metabolic diseases.…”
Section: Organoid Applicationsmentioning
confidence: 99%
“…Genetic mutations, cancer microenvironment, immune, and therapeutic selection pressures all dynamically contribute to tumor heterogeneity. Heterogeneity may lead to cells with a differential molecular signature within single tumor tissue, and in some cases, it may contribute to therapy resistance [3]. Therefore, deciphering LUAD heterogeneity will have a significant impact in designing precision medicine strategy.…”
Section: Introductionmentioning
confidence: 99%